Komunikasi Pembelajaran Fikih Ibadah melalui Demonstrasi Berbasis Video Step-by-Step dalam Meningkatkan Keterampilan Praktik Wudhu dan Sholat Peserta Didik - Mohammad Rofiq; Mashfufatur Rohmah; Sayidatur Rohmah (An-Nahdloh: Journal of Education and Islamic Studies, 2026)
Islamic jurisprudence (fiqh al-'ibadah) learning requires students not only to understand Islamic legal concepts but also to perform acts of worship correctly in accordance with Islamic teachings. Therefore, instructional communication plays a crucial role in connecting knowledge transmission with the development of practical skills. This study aims to analyze the instructional communication process in Islamic jurisprudence learning through step-by-step video-based demonstrations, examine the interaction patterns between teachers and students, and explain their contribution to students' ablution (wudhu) and prayer (shalat) practice skills. This study employed a qualitative approach using a library research design by reviewing scholarly articles, academic books, and other relevant scientific sources, particularly those published between 2021 and 2026. The collected data were analyzed using content analysis and thematic analysis to identify major themes and synthesize previous research findings. The results indicate that instructional communication is implemented through six interconnected stages: learning orientation, conceptual explanation, video-based demonstration, guided practice, feedback, and reflection. The interaction pattern is characterized as dialogic, interactive, collaborative, and multimodal through the integration of verbal communication, visual media, nonverbal cues, and direct practice. Furthermore, instructional communication contributes to strengthening conceptual understanding, improving psychomotor skills, and fostering the internalization of Islamic values in students' worship practices. This study concludes that instructional communication serves as an integrative component that determines the effectiveness of step-by-step video-based demonstrations in Islamic jurisprudence learning. These findings provide a conceptual foundation for developing more innovative, interactive, and practice-oriented instructional strategies in Islamic Religious Education. Keywords: Instructional Communication; Islamic Jurisprudence Learning; Demonstration Method; Step-By-Step Video; Practical Skills